COST EFFECTIVENESS OF ORAL PERICALCITOL IN PATIENTS WITH STAGE III-IV CHRONIC KIDNEY DISEASE AND SECONDARY HYPERPARATHYREOSIS - A. V. Rudakova (Фармакоэкономика, 2015)
results of clinical trials demonstrate that selective vitamin D receptor agonist paricalcitoldecreases proteinuria in patients with chronic kidney disease (CKD) and hyperparathyreosis.